Comparison between aluminum chloride and tetryzoline hydrochloride for control of vertical gingival displacement and crevicular fluid - MORAES MELO NETO,Clóvis Lamartine de (2017)
Abstract Introduction The use of a gingival displacement cord with a gingival displacement substance is a common procedure for taking a quality impression of the cervical terminal in teeth for prosthetic purposes. Objective To evaluate whether the mechanical-chemical method with 0.05% tetryzoline hydrochloride or 25% aluminum chloride is capable of reducing crevicular fluid, and displacing a statistically significant larger quantity of gingival tissue vertically, compared with the mechanical method (without chemical substances). Material and method Ten patients were selected, and then No. 000 and 1 Ultrapak cords were randomly positioned on teeth 13, 21 and 23. Group I – cord with no chemical substance; Group II – cords impregnated with tetryzoline hydrochloride and Group III – cords impregnated with aluminum chloride. Using dental stone models, thirty images were captured with a camera coupled to a loupe to analyze the degree of gingival displacement. Crevicular fluid was quantified using a high-precision scale and individualized strips of absorbent paper for each tooth on which gingival displacement was performed. Result There was no statistical difference between the three groups relative to the amount of vertical gingival displacement (Anova, p=0.26). As regards reduction in crevicular fluid, there was no difference between the test and control groups (Wilcoxon and Friedman, p < 0.05). Conclusion The use of tetryzoline hydrochloride or aluminum chloride to impregnate the gingival displacement cord did not improve the quantity of vertical gingival displacement and did not reduce the amount of crevicular fluid.